The Effect of Ionizing Radiation on Microorganism in some spices - AL.Bayatti, khalid K. (The Iraqi Journal of Veterinary Medicine, 2009)
The present study was undertaken to evaluate the use of ionizing radiation in decontaminating thetotal microbial burden of Capsicum peppers (Capsium annuum), Caraway (Carum carvi), and Clove(Dianthus caryphyllus). The spices were irradiated in polyethylene bags with 5KGy and 10KGy ofgamma radiation from Co-60 irradiator. Total number of bacteria and molds survived per gram ofspices after irradiation were calculated. Results showed that 5KGy gamma radiation reduced the totalnumber of bacteria by 95-98% and the number of molds and yeast by 62.8-98.2%, while 10KGyreduced the total number of bacteria by 95.5-99.9% and the number of the molds and yeast by 67-99.7%. These percentages are accepted within the maximum permissible microbial counts for humanconsumption except mold and yeast counts in caraway which its number was still more than themaximum permissible count for human consumption, and the doses used in these experiments have nosignificant changes on the sensory quality of the spices.